Assessing the Rheological Behavior of Bio-Asphalt Binder with Integrating Biowaste-Derived Activated Carbon - Patil Dipali; Hedaoo Namdeo (Civil and Environmental Engineering)
Current endeavors are being made to develop substitute asphalt binders using different biomass sources for upcoming flexible pavement construction, propelled by sustainability and the escalating expenses of traditional petroleum-centered asphalt. The primary objective of this research is to explore the feasibility of employing activated carbon (ATC) produced from biowaste, specifically walnut shells and sawdust, as a modification for petroleum-based virgin asphalt binders through chemical, physical, and rheological assessments. A comprehensive array of evaluations was carried out, encompassing examinations of homogeneity, physical characteristics, Carbon, Hydrogen, Nitrogen, Sulphur, and Oxygen (CHNSO) analysis, proximate analysis, infrared spectroscopy, multiple stress creep and recovery (MSCR), rheological attributes, and temperature sweep. The CHNSO analysis provided the elemental composition and helped develop molecular formulas for ATC. The results show that binders modified with ATC exhibited a heightening carbon content proportionate to the AC ratio, analyzed at 5%, 10%, and 15%. Temperature sweep tests revealed that adding AC significantly increased binder stiffness in accordance with the complex modulus (G*) and phase angle (δ). This increased rigidity from the ATC modification declines the temperature susceptibility of the modified binders.